The Church «sui iuris». A new canonical concept - Campo Ibáñez, S.J., Miguel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The canonical concept «sui iuris Church», whose positive implementation was brought about with the promulgation of The Code of Canons of the Eastern Churches (CCEO), has come to reflect, in canonical language, the historical tradition and conciliar teaching of the peculiar ecclesiological statute of the Eastern Churches within the Catholic communion. This article treats the process that led to the positive implementation of this concept, especially in relation to the concept «particular Church», as well as the hallmarks of the concept «sui iuris Church»: «the organized association of particular Churches under the guidance of a hierarch, within an Eastern ritual tradition, to whom the Church has recognized, explicitly or implicitly, this peculiar statute of autonomy» (sui iuris). This article also addresses the relationship between the concept «sui iuris» Church and «rite», the current reality of the sui iuris Churches, and raises some open questions, such as the possible application of the concept to other ecclesial realities, or the question concerning whether the Latin Church is another sui iuris Church.
Keywords: sui iuris Church; particular Church; rite; Eastern Catholic Churches; typology of sui iuris Churches